Il contributo delle nuove interpretazioni di Gramsci alla delineazione della strategia politica contemporanea - Balsa, Juan Javier (2019)
This article analyzes the main aspects of the so called “philological” readings of Gramsci’s Prison Notebooks and their possible contributions to think about political strategy. The first group of innovations of these readings is composed by the abandonment of the structure-superstructure metaphor, the relativization of the concept of “law”, and a more accurate notion of “crisis”. The second group of contributions is made up of the conceptualization of hegemony as relations of forces and as a struggle for hegemony, the relativization of the concept of “historical bloc”, and the clarification of the relationship between civil society and political society. And, finally, the third group of innovations comprehends the development of a perspective that think the hegemony as subjectivity's construction and that differentiates between different types of hegemony.